Hindi, asked by Anonymous, 4 months ago

( 2.5p - 1.5q )² - ( 1.5p - 2.5q )²


❌don't Spam ❌



please​

Answers

Answered by ma1431138
1

Explanation:

=(2.5p-1.5q)²-(1.5p-2.5q)²

=6.25p²+2.25q²-3.75pq-(2.25p²+6.25q²-3.75pq)

=6.25p²+2.25q²-3.75pq-2.25p²-6.25q²+3.75pq

=4p²-4q²

=(2p)²-(2q)²

=(2p+2q)(2p-2q)

Answered by purnapushkalam1991
0

Explanation:

( 2.5p - 1.5q )² - ( 1.5p - 2.5q )²

(sub (a-b) ^2=a^2-2ab+b^2

=6.25p2-7.5pq+2.25q^2-(2.25p^2-7.5pq+6.25q^2)

=6.25p2-7.5pq+2.25q^2-2.25p^2+7.5pq-6.25q^2

on solving

=4p^2-4q^2=4(p^2-q^2)

Similar questions